Information-seeking behaviour of Faculty of Agriculture and Natural Resources' students at Neudamm Campus, University of Namibia - Uugwanga, Nekulu Selma Takatsu (Library and Information Studies Centre (LISC), 2017)
This study investigated the information-seeking behaviour of the Faculty of Agriculture and Natural Resources' (FANR) students at Neudamm Campus, University of Namibia (UNAM). It determined their information needs, informationseeking patterns, information use and information evaluation including preferences for information resources. In addition, it considered the challenges students encountered when accessing and using information at Neudamm Library. This was done in order to improve the delivery of information services. Taking a qualitative research approach, this study was guided by Kuhlthau's (2004) Information Search Process model which served as a theoretical framework. Data were collected from a purposively selected sample through focus group discussions that were held with undergraduate students and interviews with postgraduate students and academic staff. The key findings from this analysis are that FANR students need information to write assignments, class tests, examinations and research projects. They value both printed and online resources. However, they are frustrated by the outdated resources, shortage of printed materials, and the limited and restricted access to e-resources. When in the library, they mainly browse for books on library shelves and search for information on the internet, and rarely use library electronic databases. There is a need to train students on the formulation of search strategies and the use of library e-resources. It transpired that students seldom use advanced search strategies, instead they either type short keywords or long sentences on Google search engine. Their challenges include very noisy library study area, ineffective interlibrary loan systems and fellow students' unwillingness to share facilities such as computers. The findings indicate that the library needs to acquire the latest e-resources, provide robust information literacy training and redesign its space to increase study space that students can use to access quality information. Additionally, the university should source funds from external donors to build a state of the art library to accommodate the increasing number of FANR students.